The Persistent Eruption of UGC 2773-OT: finally, a decade-long extragalactic Eta Carinae analogue. Issue 4 (30th November 2015) - Smith, Nathan; Andrews, Jennifer E.; Mauerhan, Jon C.; Zheng, WeiKang; Filippenko, Alexei V.; Graham, Melissa L.; Milne, Peter
Abstract: While supernova (SN) impostors resemble the Great Eruption of η Carinae in the sense that their spectra show narrow H lines and they have typical peak absolute magnitudes of −13 to −14 mag, most extragalactic events observed so far are quite different from η Car in duration. Their bright phases typically last for ∼100 d or less, rather than persisting for several years. The transient object UGC 2773-OT (discovered in 2009) had a similar peak absolute magnitude to other SN impostors, but with a gradual 5-yr pre-discovery rise. In the ∼6 yr since discovery, it has faded very slowly (0.26 mag yr −1 ). Overall, we suggest that its decade-long eruption is so far the best-known analogue of η Car's 19th century eruption. We discuss extensive spectroscopy of the ongoing eruption. The spectra show interesting changes in velocity and line shape that we discuss in detail, including an asymmetric Hα emission line that we show is consistent with the ejection of a bipolar nebula that could be very much like the Homunculus of η Car. Moreover, changes in the line width, line profile, blue excess emission resembling that of Type IIn SNe, and the intensity of Hα suggest the presence of strong circumstellar interaction in the eruption at late times. This supports the hypothesis that the extended plateau of η Car's eruption may have been powered by shock interaction as well. One interesting difference compared to η Car, however, is that UGC 2773-OT so far does not exhibit the repeated brief spikes in luminosity that have been associated with binary periastron events.